1986
DOI: 10.1002/jso.2930310407
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemo‐lmmunotherapy in stage II carcinoma of the breast

Abstract: From July of 1974 to June of 1978, 131 patients with Stage II carcinoma of the breast were randomly assigned to one of three treatment arms in order to assess the efficacy of adding immunotherapy to adjuvant chemotherapy. All patients had metastases in the axillary lymph nodes, but no clinical evidence of systemic disease. Prognostic factors were relatively equally distributed among the three treatment arms. All patients received adjuvant chemotherapy consisting of cytoxan, methotrexate, and 5-fluorouracil (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The only randomised study which reported a statistically significant improvement of DFS and OS has been presented by Klefstr6m [9] in a series of 120 stage III-breast cancer, all others studies [10,11] do not show any difference. A deleterious effect on DFS has been demonstrated by the Danish breast cancer cooperative group [12].…”
Section: Discussionmentioning
confidence: 99%
“…The only randomised study which reported a statistically significant improvement of DFS and OS has been presented by Klefstr6m [9] in a series of 120 stage III-breast cancer, all others studies [10,11] do not show any difference. A deleterious effect on DFS has been demonstrated by the Danish breast cancer cooperative group [12].…”
Section: Discussionmentioning
confidence: 99%